Черный легион Каллисто - Картер Лин (Science fiction and fantasy, 1996)
Экземпляры: ф.14 (1997) / Инвентарный номер: 39699 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 27 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445.1